Transformational Leadership in Improving Teacher Performance in Madrasah - Yahya, Sofyan (International Journal on Advanced Science, Education, and Religion, 2024)
This study aims to analyze the application of transformational leadership in improving teacher performance in madrasahs. Transformational leadership is known as an approach that motivates and inspires individuals to achieve common goals through positive changes in attitudes, behaviors, and commitments. This study uses a qualitative approach with case studies in several madrasahs in certain areas. Data were collected through in-depth interviews with madrasah principals, teachers, and observations of classroom learning activities. The results of the study indicate that transformational leadership has a significant effect on teacher motivation and performance. The application of leadership principles such as providing a clear vision, recognition of achievement, intellectual stimulation, and empowering teachers in decision-making has improved the quality of learning and teacher professional development. Teachers who feel emotional and professional support feel more motivated to give their best in their teaching. In addition, training and career development provided by the madrasah principal also enrich teachers' teaching skills and improve student learning outcomes. However, this study also identified several challenges in implementing transformational leadership, including limited resources and cultural barriers that hinder change. This study suggests the need for further support from various parties, including parents of students and other educational institutions, to realize sustainable change in madrasahs. Overall, the results of this study indicate that transformational leadership has great potential to improve teacher performance and the quality of education in madrasas.